Probabilistic study of premature shear failure of slender reinforced concrete one-way slabs subjected to blast loading - LOZANO, Fabio; JOHANSSON, Morgan; LEPPÄNEN, Joosef; PLOS, Mario (Frontiers of Structural and Civil Engineering, 2025)
Blast-loaded reinforced concrete (RC) slabs should fail under a ductile bending mechanism enabling high energy absorption capacity. Hence, brittle shear failure must be avoided. However, due to the uncertainties related to the materials, geometry, and resistance models, it may be difficult to predict which failure mode will prevail. This study analytically estimated the probability of premature flexural shear failure of slender RC one-way slabs subjected to blast loading considering such uncertainties and using the Monte Carlo method. The resistance models in Eurocode 2 were adopted. Specimens with and without shear reinforcement were analyzed. Bending failure was shown to be the most likely failure mode in the studied slabs. However, the probability of shear failure developing before bending failure was still relatively high, particularly for slabs without stirrups. To increase the confidence level concerning the preferred failure mechanism, the article proposes an overstrength factor to magnify the shear demand of the blast-loaded RC slab. Values of the overstrength factor for different target reliability levels were calculated. The study also found that the probability of premature shear failure increased with increasing amount of longitudinal reinforcement and decreasing slenderness. Likewise, greater impulse was found to enhance the risk for shear failure.